2001
DOI: 10.1161/01.cir.103.15.1972
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Value of Radionuclide Angiography in Patients With Right Ventricular Arrhythmias

Abstract: Background-The prognosis of patients with right ventricular (RV) arrhythmias remains uncertain. This study prospectively evaluated the prognostic value of RV and left ventricular (LV) involvement assessed by radionuclide angiography (RNA) as predictors for sudden death. Methods and Results-Patients (nϭ188) with severe arrhythmias originating from the RV were followed up for a mean of 45Ϯ34 months. Data on clinical presentation, resting and stress ECG, signal-averaged ECG, 24-hour Holter monitoring, and program… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(4 citation statements)
references
References 33 publications
(28 reference statements)
0
3
0
1
Order By: Relevance
“…В многоцентровом исследовании, посвященном вопросам прогностической оценки результатов равновесной радионуклидной томовентрикулографии у пациентов с правожелудочковыми аритмиями, было показано, что наличие зон диссинхронии в миокарде желудочков является независимым прогностическим фактором внезапной сердечной смерти и синкопальных состояний [59]. При этом другие инструментальные (ЭКГ, Холтеровское мониторирование) и клинические (выраженность симптомов нарушения ритма сердца, частота эпизодов желудочковой тахиаритмии и др.)…”
Section: исследованиеunclassified
“…В многоцентровом исследовании, посвященном вопросам прогностической оценки результатов равновесной радионуклидной томовентрикулографии у пациентов с правожелудочковыми аритмиями, было показано, что наличие зон диссинхронии в миокарде желудочков является независимым прогностическим фактором внезапной сердечной смерти и синкопальных состояний [59]. При этом другие инструментальные (ЭКГ, Холтеровское мониторирование) и клинические (выраженность симптомов нарушения ритма сердца, частота эпизодов желудочковой тахиаритмии и др.)…”
Section: исследованиеunclassified
“…It has been reported that very small structural or functional abnormalities of the RV can be related to ARVD [17][18][19][20] even in the absence of RV dilatation or RVEF alteration. Based on a topographical analysis of the RV kinetics for a small and localized dyskinetic area, mainly in the 3D tomographic approach, such cases will completely be missed by our method based on global ventricular data.…”
Section: Limits Of the Studymentioning
confidence: 99%
“…The multiplicity of reasons for suspecting ARVD leads to the necessity of a non invasive screening method, and radionuclide gated ventriculography (RNV) has excellent features to be a good candidate as a screening method: ability of precise measurement of both left and right ejection fractions, simultaneous biventricular imaging for ventricular volumes and regional wall motion appreciation, assessment of inter-and intraventricular synchronism through phase analysis [13][14][15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…RNA RV phase analysis was the only variable able to predict death and the addition of an LV abnormality significantly increased the risk. 5 Mechanical dyssynchrony is not equivalent to electrical dyssynchrony even if both often concur. Indeed, the latter is defined by an asynchronous electrical activation illustrated by a prolonged QRS duration ([ 120 ms) and studies have shown that mechanical dyssynchrony could exist in more than a third of patients with normal QRS duration.…”
mentioning
confidence: 99%